2007
DOI: 10.1007/bf03033901
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic effects of nicotine in its protection against salsolinol-induced cytotoxicity

Abstract: Salsolinol (1-methyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline), a metabolite of dopamine, may act as an endogenous neurotoxin and contribute to the etiology of Parkinson's disease (PD). The inverse relationship between smoking and PD prompted our previous investigation and the report of protective effects of nicotine against salsolinol-induced toxicity in cultured SH-SY5Y cells (Copeland et al., Neurotox. Res. 8:289, 2005). These cells, derived from human neuroblastoma cells, express dopaminergic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 20 publications
4
39
1
Order By: Relevance
“…Non-smokers develop Parkinson's Disease at twice the frequency of smokers [39][40][41]. Animal studies show that cigarette smoke protects against MPTP-induced neurotoxicity in the dopaminergic nigrostriatal system, possibly by protecting neurons against oxidative damage caused by the metabolism of dopamine [42][43][44]. Nicotine has been shown in neuronal cultures to offer protection against neurotransmitter-related excitotoxicity [45,46], and against arachadonic acid [47].…”
Section: Discussionmentioning
confidence: 97%
“…Non-smokers develop Parkinson's Disease at twice the frequency of smokers [39][40][41]. Animal studies show that cigarette smoke protects against MPTP-induced neurotoxicity in the dopaminergic nigrostriatal system, possibly by protecting neurons against oxidative damage caused by the metabolism of dopamine [42][43][44]. Nicotine has been shown in neuronal cultures to offer protection against neurotransmitter-related excitotoxicity [45,46], and against arachadonic acid [47].…”
Section: Discussionmentioning
confidence: 97%
“…A previous study demonstrated that CIQs, such as salsolinol and NM-salsolinol are promising endogenous neurotoxins that may lead to the development of PD (19). Thus, a ̔vicious̓ cycle may be induced by CIQs.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was quantitatively determined using a 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay as described in detail previously (Copeland et al 2005(Copeland et al , 2007. Briefly, cells (1.5 9 10 4 cells per well) were plated in a 96-well plate in above media.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…The observance of high levels of salsolinol in the cerebrospinal fluid of patients with PD has led to the suggestion that salsolinol might be involved in the etiology or loss of dopamine neurons in at least some Parkinson patients (Storch et al 2002;Maruyama et al 2004). A neuroprotective effect of nicotine against salsolinol-induced toxicity in immortal SH-SY5Y cells was recently reported (Copeland et al 2005(Copeland et al , 2007. SH-SY5Y cells, derived from human neuroblastoma cells are extensively used as a model to study nigral dopaminergic neurons as they express high level of dopaminergic activity (Storch et al 2002;Maruyama et al 2004;Naoi et al 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation